2013
DOI: 10.1534/genetics.113.151381
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Variation of Cytosine Modifications Between European and African Populations and the Implications for Complex Traits

Abstract: Elucidating cytosine modification differences between human populations can enhance our understanding of ethnic specificity in complex traits. In this study, cytosine modification levels in 133 HapMap lymphoblastoid cell lines derived from individuals of European or African ancestry were profiled using the Illumina HumanMethylation450 BeadChip. Approximately 13% of the analyzed CpG sites showed differential modification between the two populations at a false discovery rate of 1%. The CpG sites with greater mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
137
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 45 publications
7
137
1
Order By: Relevance
“…Genetic variation has been shown to contribute to longevity, evidenced by the fact that longevity runs in families (Schoenmaker et al ., 2006). Clear relationships also exist between DNA methylation and genetic variability, and recent studies have identified genetic loci whose variation is strongly associated with DNA methylation at nearby sites (Fraser et al ., 2012; Gamazon et al ., 2013; Gutierrez Arcelus et al ., 2013; Moen et al ., 2013). Thus, it is possible that genetic variants associated with longevity may also be correlated with DNA methylation changes.…”
Section: Considerations For Studies Of Epigenetics and Agingmentioning
confidence: 99%
“…Genetic variation has been shown to contribute to longevity, evidenced by the fact that longevity runs in families (Schoenmaker et al ., 2006). Clear relationships also exist between DNA methylation and genetic variability, and recent studies have identified genetic loci whose variation is strongly associated with DNA methylation at nearby sites (Fraser et al ., 2012; Gamazon et al ., 2013; Gutierrez Arcelus et al ., 2013; Moen et al ., 2013). Thus, it is possible that genetic variants associated with longevity may also be correlated with DNA methylation changes.…”
Section: Considerations For Studies Of Epigenetics and Agingmentioning
confidence: 99%
“…Methylation levels at ;50% of these population-specific CpGs are explained by divergence in allele frequencies at cis-acting SNPs between populations . Studies of methylation differences using Illumina InfiniumHumanMethylation450 BeadChip array data from 133 lymphoblastoid cell lines from European and African HapMap samples found that 13% of analyzed CpGs showed significant methylation differences between the populations, >50% of which were in methQTLs with local SNPs (Moen et al 2013). CpGs showing differential methylation levels across ethnicities are more likely to be driven by genotype than other CpGs (Heyn et al 2013).…”
mentioning
confidence: 99%
“…These genetic differences among ethnic populations have motivated additional studies to adjust the recommended drug dosage depending on the population [15]. Ethnic differences are also a vital feature of DNA methylation [16][17][18][19]. However, the mechanism through which these differences influence the effect of DNA methylation on the treatment response and the drug ADME remains largely unknown.…”
mentioning
confidence: 99%
“…Because methylation patterns are tissue specific [20] and most of the current MeDR genes are related to cancers, we analyzed differential methylation (DM) between African ancestry (AA) and European ancestry (EA) populations in two sources of samples. The first source contained the primary tumor tissues of four cancer types (breast invasive carcinoma [BRCA], colon adenocarcinoma [COAD], head and neck squamous cell carcinoma [HNSC] and uterine corpus endometrial carcinoma [UCEC]) from The Cancer Genome Atlas (TCGA) [21][22][23][24], and the second source contained lymphoblastoid cell lines (LCLs) of general populations from the International HapMap Project [17]. We also investigated the relationship between DNA methylation and gene expression and discussed the influence of DNA methylation on the treatment response and drug ADME.…”
mentioning
confidence: 99%